2005
DOI: 10.1063/1.1942492
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide foldings obtained with effective pair potentials

Abstract: We present a model of protein folding which is based on a potential function that describes the effective interaction between two amino acids (alanines, in this case). Our model is consistent with the formation of two important secondary structures, namely, an alpha-helix and a beta-ladder. In each case, we estimate the density of states using a random walk in energy space. This function allows the direct calculation of certain thermodynamic properties. By means of the configurational temperature, we also veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…(10) and also the traditional kinetic temperature based on the particle momenta) and statistically reliable (i.e., less affected by system-size effects). Thus it has been applied to a number of physical systems (e.g., chain molecules [51], charge-stabilized colloidal systems [52], polypeptides [53], gravitationally-driven inhomogeneous systems [54], flowing polymeric melts [55], etc.) under equilibrium or nonequilibrium conditions.…”
Section: Configurational Temperaturementioning
confidence: 99%
“…(10) and also the traditional kinetic temperature based on the particle momenta) and statistically reliable (i.e., less affected by system-size effects). Thus it has been applied to a number of physical systems (e.g., chain molecules [51], charge-stabilized colloidal systems [52], polypeptides [53], gravitationally-driven inhomogeneous systems [54], flowing polymeric melts [55], etc.) under equilibrium or nonequilibrium conditions.…”
Section: Configurational Temperaturementioning
confidence: 99%
“…However, with the advent of algorithms capable of escaping energy minima, such as the multicanonical 23 and Wang-Landau algorithms, 24 it possible to address the coupling of transition in macromolecular systems using stochastic approaches such as Monte Carlo simulations. In particular, the Wang-Landau algorithm and various modifications of it have been extensively used to address studies on lattice models, 25 united atom models for proteins, 26 ring polymers, 27 HP model, 28 RAFT model, 29 pair potentials for proteins, 30 sequence based and structure based energy functions for proteins, 31 the collapse of semiflexible 15 and flexible 16 polymers, etc. Recently, we have proposed a minimal model 32 to model the helix-coil transition in homopolypeptides using Monte Carlo simulations based on the Wang-Landau sampling algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the environment surrounding an alanine inside a protein can be considered to be hydrophobic, to some extent. In other words, our model is not suitable to describe the behavior of polyalanines in aqueous solution, which is still the subject of intense debate in the literature. , Our model, however, predicts the formation of α-helices for a single chain of bulk-like polyalanines, and we found, in actual proteins, some sequences of polyalanines (located far from the ends) with the α-helical conformation . On the other hand, Soto et al recently found that the polyalanine monomer preferentially adopts a β-hairpin structure in a fully hydrophobic, nonpolar solvent (cyclohexane).…”
Section: Introductionmentioning
confidence: 72%
“…Other successful approaches have included experimental information that can be either discrete (contact potentials) or continuous, as in this work (see, for example, ref for a recent review). In its present form, our model is the two-component generalization of a previous work in which we were able to reproduce two secondary motifs of a one-component system (polyalanines) …”
Section: Introductionmentioning
confidence: 98%